Reinvestigation of the type material for Odontidium hyemale (Roth) Kützing and related species, with description of four new species in the genus Odontidium (Fragilariaceae, Bacillariophyta) - Jüttner, Ingrid; Williams, David M.; Levkov, Zlatko; Falasco, Elisa; Battegazzore, Maurizio; Cantonati, Marco; van De Vijver, Bart; Angele, Catalena; Ector, Luc (Phytotaxa, 2015)
The type materials of Odontidium hyemale, Odontidium anomalum var. longissimum (longissima), Diatoma hiemale var. maxima (maximum), Odontidium anomalum, and additional materials from the Faroe Islands, Austria, Switzerland, Italy and Macedonia were studied in LM and SEM. The nomenclature of these taxa is explained and original drawings presented. In addition, two new species, Odontidium rostratum and Odontidium apiculatum are described from Macedonia and Italy. The history and taxonomic changes of Odontidium are presented and its separation from Diatoma at the genus level explained in more detail.